A rare case of neoplastic transformation in a longstanding case of fistula-in-ano - Gupta, Neeru; Gupta, Chhaya; Sud, Aruna (Annals of Pathology and Laboratory Medicine, 2015)
Mucinous adenocarcinoma development in a long standing case of with fistula-in-ano is rare. A case of fistula–in-ano diagnosed as low grade mucinous adenocarcinoma on biopsy and confirmed on Immunohistochemistry is discussed. It was established that the carcinoma had developed within the fistula and was not a secondary manifestation of any other tumor.